2010
DOI: 10.1007/s10439-009-9874-z
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics of Dual-Axis Cervical Accelerometry Signals

Abstract: Dual-axis swallowing accelerometry is a promising noninvasive tool for the assessment of difficulties during deglutition. The resting and anaerobic characteristics of these signals, however, are still unknown. This paper presents a study of baseline characteristics (stationarity, spectral features, and information content) of dual-axis cervical vibrations. In addition, modeling of a data acquisition system was performed to annul any undesired instrumentation effects. Two independent data collection procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 48 publications
1
59
0
Order By: Relevance
“…From a physiological stand point, the S-I axis appears to be as worthy of investigation as the A-P axis because the maximum excursion of the the hyolaryngeal structure during swallowing is of similar magnitude in both the anterior and superior directions [36,37]. Recent contributions have indeed confirmed that dual-axis accelerometers yield more information and enhance analysis capabilities [38][39][40][41][42][43].…”
Section: Swallowing Accelerometrymentioning
confidence: 99%
“…From a physiological stand point, the S-I axis appears to be as worthy of investigation as the A-P axis because the maximum excursion of the the hyolaryngeal structure during swallowing is of similar magnitude in both the anterior and superior directions [36,37]. Recent contributions have indeed confirmed that dual-axis accelerometers yield more information and enhance analysis capabilities [38][39][40][41][42][43].…”
Section: Swallowing Accelerometrymentioning
confidence: 99%
“…Many studies, in fact, utilize the raw transducer signal to draw their conclusions and many used the human ear in the analysis without any digital or mathematical analysis of the signal waveform’s characteristics [14]–[17], [19], [20], [22], [27], [32]–[37], [40], [48], [50], [52], [63], [76]–[79], [91]–[112]. Those studies that have conditioned the signal between acquisition and analysis generally only applied a bandpass filter in order to eliminate sources of noise at either end of the frequency spectrum [13], [28], [38], [39], [43]–[47], [49], [51], [53]–[62], [65], [68]–[73], [84]–[89]. Once again Takahashi, et al’s work [16], which was later supported by Youmans, et al [17], is cited often because their study characterized the frequency range of swallowing accelerometry signals.…”
Section: Signal Conditioningmentioning
confidence: 99%
“…Unfortunately, these studies have been unable to determine the lower bound on useful frequency components, resulting in much more variability of the placement of the lower notch. While some place it as low as 0.1 Hz in order to maintain a “pure” signal [21], [49], [51], [65], [66], [83], [86], [90], others place it as high as 30 Hz or more in order to eliminate motion artifacts and other low frequency noise [39], [42], [44], [60]–[62], [69]. Since similar bandlimits have yet to be identified for swallowing sounds, studies which use a microphone simply limit the recorded signal to either the human audible range [21], [32], [33], [37], [40], [46], [48], [67], [76]–[78], [86], [89], [95], [97]–[100], [102], [103], [110], [112]–[116] or the range of common stethoscopes used in bedside assessments [13], [22], [28], [39], [56], [69], [73], [88], [91], [92].…”
Section: Signal Conditioningmentioning
confidence: 99%
“…Specifically, the problem is to differentiate between safe and unsafe swallowing on the basis of dual-axis accelerometry (Damouras et al, 2010;Sejdic, Komisar, Steele & Chau, 2010). The basic idea is to decompose a high dimensional classification problem into 3 lower dimensional problems, each with a unique subset of features and a dedicated classifier.…”
Section: Discriminating Between Healthy and Abnormal Swallowsmentioning
confidence: 99%
“…• The centroid frequency of the signal S (Sejdic, Komisar, Steele & Chau, 2010) can be estimated asf…”
Section: Time-domain Featuresmentioning
confidence: 99%